2015
DOI: 10.7567/jjap.54.07he10
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the rate of sono-oxidation in the presence of CO2

Abstract: The effect of adding CO 2 to the matrix gas on the rate of sono-oxidation was examined. It is already known that CO 2 dissolved in water prevents the sonochemical reaction because of the suppression of cavitation intensity. In this study, however, it was observed that the rate of sono-oxidation of I % ions in water increased with the introduction of a small amount of CO 2 . As the matrix, Ar, He, O 2 , and N 2 were used. The improvement was confirmed for all these gases. In the case of Ar, the rate of sono-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The product yield was reduced when the mole fraction of CO 2 was increased beyond 3% and then be zero when %CO 2 > 8%. The same optimum of CO 2 (2%) in Ar was recorded by Harada and Ono for the sono‐oxidation of KI at various combinations of frequencies and powers (28 kHz and 100 W, 200 kHz and 100 W, 200 kHz and 15 W, 2.4 MHz and 15 W). In the work of Harada and Ono, the oxidation yield at 2.4 MHz drops quickly at 5% CO 2 and falls to zero for %CO 2 > 20%.…”
Section: Resultssupporting
confidence: 68%
“…The product yield was reduced when the mole fraction of CO 2 was increased beyond 3% and then be zero when %CO 2 > 8%. The same optimum of CO 2 (2%) in Ar was recorded by Harada and Ono for the sono‐oxidation of KI at various combinations of frequencies and powers (28 kHz and 100 W, 200 kHz and 100 W, 200 kHz and 15 W, 2.4 MHz and 15 W). In the work of Harada and Ono, the oxidation yield at 2.4 MHz drops quickly at 5% CO 2 and falls to zero for %CO 2 > 20%.…”
Section: Resultssupporting
confidence: 68%
“…These findings may be understood by considering CO 2 to be a radical scavenger, that is, if CO 2 quenches •H, then •OH will remain and oxidise the reactants. This is shown in reactions (17) and (18) which are those that occur under Ar in water, reactions (19) and (20) show how •OH contributes to oxidation while •H is consumed by the CO 2 [95].…”
Section: Gas Mixturesmentioning
confidence: 93%
“…Henglein in an earlier paper also considered that CO 2 amounts greater than 3% resulted in decreased sonochemical yields [221]. In another other study, it was concluded that the effect of small amounts of CO 2 in argon at 200 kHz and 100 W can lead to an increase I ି production up to seven fold [95]. These findings may be understood by considering CO 2 to be a radical scavenger, that is, if CO 2 quenches •H, then •OH will remain and oxidise the reactants.…”
Section: Gas Mixturesmentioning
confidence: 96%
See 2 more Smart Citations